2010
DOI: 10.1111/j.1750-3841.2010.01918.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Volatile Spoilage Metabolites in Fermented Cucumbers Using Nontargeted, Comprehensive 2‐Dimensional Gas Chromatography‐Time‐of‐Flight Mass Spectrometry (GC×GC‐TOFMS)

Abstract: A nontargeted, comprehensive 2-dimensional gas chromatography-time-of-flight mass spectrometry (GC×GC-TOFMS) method was developed for the analysis of fermented cucumber volatiles before and after anaerobic spoilage. Volatile compounds extracted by solid-phase microextraction were separated on a polyethylene glycol 1st-dimension column and 14% cyanopropylphenyl 2nd-dimension column. Among 314 components detected in fermented cucumber brine, 199 had peak areas with coefficients of variation below 30%. Peak ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 39 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…Acetic acid is one of the end products of that metabolism (37), which is consistent with the increased concentrations of acetic acid in the spoiled commercial fermentations presenting high counts of MB1 colonies. Although 1,2-propanediol has been identified as a metabolic product of lactic acid degradation by L. buchneri (37), previous characterization of the metabolites in spoiled fermented cucumber samples did not detect this alcohol (23)(24)(25). This alcohol can subsequently be converted into propionic acid by other microorganisms belonging to the lactobacillus family.…”
Section: Discussionmentioning
confidence: 98%
“…Acetic acid is one of the end products of that metabolism (37), which is consistent with the increased concentrations of acetic acid in the spoiled commercial fermentations presenting high counts of MB1 colonies. Although 1,2-propanediol has been identified as a metabolic product of lactic acid degradation by L. buchneri (37), previous characterization of the metabolites in spoiled fermented cucumber samples did not detect this alcohol (23)(24)(25). This alcohol can subsequently be converted into propionic acid by other microorganisms belonging to the lactobacillus family.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Koek et al (2008) found that a polar/nonpolar column combination resulted in better resolution of components and greater use of the separation space with similar separation efficiency. This technology has been successfully adapted for the nontargeted profiling of volatile compounds in fermented cucumber ( Johanningsmeier & McFeeters 2011) and metabolic footprinting of Lactobacillus buchneri during fermented cucumber spoilage ( Johanningsmeier & McFeeters 2015), resulting in the identification of 92 volatile and nonvolatile compounds related to spoilage from several thousand metabolite peaks detected.…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 99%
“…Productions of unpleasant odour and plant cell wall degrading enzymes (PCWDEs) are the well-characterised biochemical activities of vegetable spoilage organisms (Johanningsmeier & McFeeters, 2011;Lee et al, 2013). But the growth of these undesirable organisms is always inhibited by the acid stress thanks to the low-pH environment of pickle product (Fleming et al, 1983).…”
Section: Introductionmentioning
confidence: 99%